Development of Game-Based Football Learning Materials Containing Character Values ​​at State Elementary School 168 Palembang - A.Rahman Sayuti; Meirizal Usra; Iyakrus Iyakrus; Reza Resah Pratama; Wahyu Indra Bayu (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to develop football learning materials based on simple games integrated with character values for elementary school students. The research employed a Research and Development (R&D) method using the 4D model consisting of define, design, develop, and disseminate stages. The developed materials focused on dribbling and kicking techniques integrated with character values such as healthy lifestyle awareness, mutual respect, humility, tolerance, and anti-violence attitudes. The research subjects involved material experts, media experts, PJOK teachers, and students at SD Negeri 168 Palembang. Data were collected through validation sheets, questionnaires, and observation instruments. The results showed that the developed learning materials were categorized as very valid based on material expert and media expert assessments. The learning materials were also considered feasible and practical for implementation in football learning activities. The integration of character values through game-based activities increased students’ enthusiasm, participation, and engagement during learning. Therefore, the developed football learning materials can be used as an innovative learning resource to support meaningful and character-oriented PJOK learning in elementary schools.